Learning Interest: How Does the Effective of the Game-Based Learning and Team Games Tournament Models? - Alfina Amalia Azizah; Nurul Azizah; Baharudin Baharudin; Nur Asiah; Jamal Fakhri (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2025)
Education in Indonesia is a fundamental right crucial for national development. Despite continuous progress, the quality of education still faces significant challenges, such as a lack of facilities, infrastructure, and professional educators. In the 5.0 era, education must become more inclusive, skill-based, and relevant to current developments. Teachers are required to develop engaging learning models to enhance students’ motivation, interest, and active participation. This study aims to determine the effectiveness of implementing Game-Based Learning (GBL) and Team Games Tournament (TGT) models on students’ interest in learning Islamic Education (IE) at SMP Negeri 23 Bandar Lampung. The research employed a quantitative approach with a quasi-experimental design. The experimental classes were VIII E and VIII F, while VIII H served as the control class. Post-test data collection used non-test instruments (questionnaires). The tests conducted included instrument tests (validity and reliability), prerequisite tests (normality and homogeneity), and hypothesis testing (One-Way ANOVA). The study results showed a reliability value of 0.696 > 0.6. In hypothesis testing using One-Way ANOVA, the significance value obtained was 0.001 < 0.005, leading to the rejection of H₀. It can be concluded that the GBL and TGT models are more effective in enhancing learning interest compared to conventional teaching methods. The implications of this study highlight the importance of integrating technology into ISLAMIC EDUCATIONlearning and the necessity for teachers to design adaptive and responsive teaching strategies. This study proposes a unique approach by combining Wordwall-based GBL and Educaplay-based TGT models, focusing on enhancing students' interest in learning Islamic education.